PENGARUH IMPLEMENTASI KEBIJAKAN E-OFFICE TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI DINAS SOSIAL KABUPATEN SUMEDANG - Azharulloh, Khairunisa (LPPM UNSAP & FISIP UNSAP, 2025)
he purpose of this study was to determine the Implementation of E-Office Policy and Employee Work Productivity, to determine the relationship between E-Office Policy Implementation and Employee Work Productivity and to determine the magnitude of the influence of E-Office Policy Implementation on Employee Work Productivity in Sumedang District Social Service. This study uses a descriptive analysis method with a quantitative approach and the type of statistics used is descriptive statistics with a non-probability sampling technique with a saturated sampling technique. The number of samples studied was 33 respondents. The analysis used includes percentage calculations, normality tests, correlation coefficient tests, significance tests, and determination coefficient tests.Based on the results of the study, it is known that the Implementation of E-Office Policy in Sumedang District Social Service is in the very good criteria with analysis results reaching 87.39%. Then for Employee Work Productivity at the Sumedang Regency Social Service is in the very good criteria with the analysis results reaching 85.06%. From the correlation analysis, a correlation value of 0.792 was obtained, indicating a positive and significant relationship between the Implementation of E-Office Policy and Employee Work Productivity at the Sumedang Regency Social Service. From the results of the significance test, a t-count value was obtained which was greater than the t table, namely 7.223>2.039. From the results of the determination coefficient analysis, it is known that the E-Office Policy Implementation variable has an influence on Employee Work Productivity of 62.8% while the remaining 37.2% is influenced by other factors not discussed in this study.